U MANAGEMENT ORGANIZATION DESSERT FROM GREEN BEAN MILK CARROT FLAVOR FOR THE ELDERLY: Manajement Organization Dessert - U Yuyun Triastuti tuti; Tri Rettagung Diana; Julia Vebrianti (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Physical and psychological changes in the elderly affect the management of food administration, especially for dessert. Dessert made from green bean milk with carrot flavor into hot pudding and cold pudding. The purpose of this study was to determine the physical characteristics and acceptance of the elderly, as well as the nutritional content of dessert. This research method uses are methods of observation, counseling, experimentation, description test, hedonic test, chemical test, and documentation. Experiment in making hot pudding using whole eggs and egg whites and cold pudding using gelatin flour and konyaku flour, as well as a combination of using low-calorie sugar, nutritional content test. The results of the research on the best characteristics of hot pudding taste sweet and savory, soft texture, distinctive aroma of green beans and carrots, and attractive brownish orange color. The cold pudding tastes sweet, has a characteristic aroma of medium carrot green beans, foamy texture, and a bright orange-white color. The results of the hedonic test showed that hot pudding with the use of whole eggs and 100 g of low-calorie sugar was the most preferred, while cold pudding with the use of konyaku and 100 g of low-calorie sugar was the most preferred. The chemical test results of the selected hot pudding contained 2.3% cholesterol, 26% vitamin A, and 10% protein, while the selected cold pudding contained 2% cholesterol, 27% vitamin A, and 12% protein.